2014
DOI: 10.2139/ssrn.2532152
|View full text |Cite
|
Sign up to set email alerts
|

Market Impacts and the Life Cycle of Investors Orders

Abstract: In this paper, we use a database of around 400,000 metaorders issued by investors and electronically traded on European markets in 2010 in order to study market impact at different scales.At the intraday scale we confirm a square root temporary impact in the daily participation, and we shed light on a duration factor in 1/T γ with γ 0.25. Including this factor in the fits reinforces the square root shape of impact. We observe a power-law for the transient impact with an exponent between 0.5 (for long metaorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 37 publications
5
80
0
Order By: Relevance
“…In Bacry, Iuga, et al. (2015), it is found that the market impact function fits a power‐law with exponent 0.45. In Gatheral et al.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In Bacry, Iuga, et al. (2015), it is found that the market impact function fits a power‐law with exponent 0.45. In Gatheral et al.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, there always exists a macroscopic PMI function and the convergence of the sequence false(MI¯T(f,·)false)T0 is equivalent to that of false(TMI¯T(f,·)false)T0. Motivated by the empirical results on market impact (Bacry, Iuga, et al., 2015; Bouchaud, 2010; Gomes & Waelbroeck, 2015; Lillo et al., 2003; Potters & Bouchaud, 2003) discussed in Section 1, we make the following natural assumption. Assumption For constant execution rate, that is f=bold1[0,s] for some s(0,1], the scaling limit of the market impact function exists pointwise and is nonincreasing after time s .…”
Section: Market Impact Is Power‐lawmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a random process whose realization consists of a sequence of isolated events with their time-stamps. Due to their generality, point processes have been widely used for modeling phenomena such as earthquakes (Hawkes 1971a), human activities (Malmgren et al 2008), financial data (Bacry et al 2015), context-aware recommendations (Du et al 2015), etc. A common property of the problems above is that the precise event time intervals can carry important information about the underlying dynamics, which otherwise are not available from the sequence of interval features that are evenly sampled from the continuous signal.…”
Section: Introductionmentioning
confidence: 99%